Study on microwave‐accelerated casein protein grafted with glucose and β‐cyclodextrin to improve the gel properties. (7th April 2015) - Bi, Weiwei; Zhao, Weili; Li, Xiaodong; Ge, Wei; Muhammad, Zafarullah; Wang, Haixia; Du, Lingling
Summary The effect of glycosylation treatment coupled with microwave heating (MH) on gel properties and structure change of casein were investigated. Conjugation was confirmed by electrophoresis. Protein disulphide bonds were broken by microwave irradiation to create an increase first and a decrease later in free sulfhydryl contents with time, thereby inducing subunit disaggregation. Also, the exposure of hydrophobic core residues was increased in MH‐treated casein, which brings about protein disaggregation and unfolding. It showed that graft reactions by MH had much faster than those by water bath heating (WH). The content of disulphide bonds is 7.2% and 6.0% in the casein–glucose and casein–β‐cyclodextrin, respectively, treated by MH which was reduced significantly than that of treated by WH. Moreover, MH can increase the hardness of the gel. Consequently, MH could improve the efficiency of the reaction and gel properties.